Analisis Pengaruh Kebijakan, Kekhawatiran, Kebiasaan Dan Promosi Terhadap Minat Belanja Konsumen Online Shop Di Era Pandemi Covid-19: Studi Kasus Mahasiswa Di Yogyakarta - Muji Setyo Jatmiko; Romadhona Ana Maghfiroh; Miswanto; Frasto Biyanto; Baldric Siregar (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
The purpose of this study was to examine whether policies, concerns, habits, and promotions affect online shopping interest. This study uses a Likert scale and is included in quantitative research. Using the IBM SPSS version 27 application for statistical calculations. The respondents obtained were 110 respondents, with 96 respondents who could be taken and 14 respondents who were not taken for reasons of not meeting the criteria. This study concluded that policies and promotions do not have a significant influence on Consumer Shopping Interest in Online Shops in the COVID-19 Pandemic Era. While concerns and habits have a significant positive influence.